2017
DOI: 10.1101/208132
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arabidopsis HIPP27 is a host susceptibility gene for the beet cyst nematode Heterodera schachtii

Abstract: SummarySedentary plant-parasitic cyst nematodes are obligate biotrophs that infect the roots of their host plant. Their parasitism is based on modification of root cells to form a hypermetabolic syncytium from which the nematodes draw their nutrients. The aim of this study was to identify nematode susceptibility genes in Arabidopsis thaliana and to characterize their roles in supporting the parasitism of Heterodera schachtii. By selecting genes that were most strongly upregulated in response to cyst nematode i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…Some previous studies have mentioned degradation of the endodermis and the presence of periderm‐like tissue around syncytia (Golinowski et al ., ; Sobczak et al ., ; Radakovic et al ., ; Różańska et al ., ). To analyze this anatomical problem in more detail, we conducted serial sectioning of samples with nematode infection sites at 3, 5 and 10 dai (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have mentioned degradation of the endodermis and the presence of periderm‐like tissue around syncytia (Golinowski et al ., ; Sobczak et al ., ; Radakovic et al ., ; Różańska et al ., ). To analyze this anatomical problem in more detail, we conducted serial sectioning of samples with nematode infection sites at 3, 5 and 10 dai (Figures and ).…”
Section: Resultsmentioning
confidence: 99%
“…Studies of the interactomes of effectors from different phytopathogens have identified common host targets, proposed to be immunity-related “hubs,” which are targeted by diverse pathogens to achieve infection ( 48 ). The movement protein of potato mop top virus interacts with NbHIPP26 to promote long-distance viral movement ( 49 ), and AtHIPP27 is reported to be a susceptibility factor for infection by the beet cyst nematode Heterodera schachtii ( 50 ). There may be more as-yet unidentified effectors, produced by diverse pathogens, which target HIPPs or HPPs to promote infection.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of the interactomes of effectors from different phytopathogens have identified common host targets, proposed to be immunity-related "hubs" which are targeted by diverse pathogens to achieve infection (48). The movement protein of potato mop top virus interacts with NbHIPP26 to promote long-distance viral movement (49), and AtHIPP27 is reported to be a susceptibility factor for infection by the beet cyst nematode Heterodera schachtii (50). There may be more as-yet unidentified effectors, produced by diverse pathogens, which target HIPPs or HPPs to promote infection.…”
Section: Hipps and Hpps May Be Plant Immunity Hubs And Are Targeted mentioning
confidence: 99%